Long-term effect of ammonia- and water-based silver fluoride on dentin collagen matrix - Uctasli, Merve; Seseogullari Dirihan, Roda; Stape; Thiago Henrique Scarabello; Mutluay; Mustafa; Murat; Tezvergil-Mutluay, Arzu (Elsevier BV, 2026)
Objective: To evaluate the long-term effect of ammonia- and water-based silver fluoride treatments on the degradation of the dentin collagen matrix.
Methods: Dentin beams (0.3x3x7mm) were demineralized (10 % H3PO4), rinsed and randomly distributed into six groups. Groups (n = 10 beams/group) were treated with (1) ammonia-based silver fluoride = SDF; (2) SDF + potassium iodide = KI (3) water-based silver fluoride = SF (4) SF + KI (5) KI (6) untreated demineralized dentin beams served as control. Following treatments, dry mass, modulus of elasticity and enzymatic activity were assessed. Dentin beams were incubated in calcium- and zinc-containing artificial saliva up to 6 months. After different incubation periods (1 week, 1 month, 3 months or 6 months), dry mass, modulus of elasticity and enzymatic activity were reevaluated. The aliquots of incubation media were analyzed to determine the solubilized telopeptides of collagen (ICTP and CTX immunoassays), hydroxyproline release and total extractable protein (Bradford assay). Scanning electron microscopy imaging and in situ zymography analyses were conducted. Data were statistically analyzed with ANOVA followed by Tukey test (α=0.05).
Results: Silver fluoride treatments reduced the total enzymatic activity, but increased the solubilized telopeptides of collagen throughout incubation periods (p < 0.05). The addition of KI exacerbated the loss of dry mass, modulus of elasticity, hydroxyproline release and total protein loss (p < 0.05).
Significance: Ammonia- and water-based silver fluoride treatments may reduce long-term degradation of dentin collagen. However, potassium iodide can further increase endogenous protease activity and compromise the structural integrity of dentin's organic matrix.
Keywords: Aqueous silver fluoride (SF); Cysteine cathepsins; Degradation; Dentin; Dentin collagen; Inactivation; Matrix metalloproteinases; Potassium iodide (KI); Proteases; Silver diamine fluoride (SDF).